The COVID‐19 pandemic‐induced behavioral restrictions and their impact on child and adolescent psychiatric units—Infection control or freedom - Masahide Usami; Yoshinori Sasaki; Mayuna Ichikawa; Miki Matsudo; Mutsumi Ohashi; Yui Higashino; Yusuke Kono; Haruna Matsudo; Yuki Nomura; Minjae Ma; Yuuki Sakoh; Maiko Odaka; et al. (PCN Reports)
Abstract Aim This study examines the impact of COVID‐19 pandemic‐induced behavioral restrictions on child psychiatric inpatients in Japan, particularly focusing on limitations placed on outings and overnight stays as infection‐control measures. Methods Data were collected from inpatients from the children's mental health registry between January 2016 and December 2022. The clinical data, such as age, gender, diagnosis, result of polymerase chain reaction (PCR) tests, frequency of outings and overnight stays before and after the pandemic, were compared. Results During the COVID‐19 pandemic, the decrease in both outings and overnight stays among child psychiatric inpatients in Japan was statistically significant. As a result, home interactions with families decreased. In addition, diagnoses of hospitalized children increased significantly in cases of eating disorders and decreased in diagnoses of autism spectrum disorders. Conclusion These results underscore the need for flexible, individualized approaches to infection control that consider the mental health of hospitalized children.